An evidence‐based approach to medicinal plants for the treatment of sperm abnormalities in traditional Persian medicine. (29th September 2016) - Tahvilzadeh, M.; Hajimahmoodi, M.; Toliyat, T.; Karimi, M.; Rahimi, R.
Summary: Infertility is defined as inability of a sexually active couple to conceive after 1 year of regular intercourse without contraception. Male factors account for 20%–50% of cases of infertility. The aim of this study was to review medicinal plants that proposed to improve sperm abnormalities in traditional Persian medicine. For this purpose, PubMed, Scopus, GoogleScholar and Cochrane library were explored for medicinal plants used in traditional Persian medicine for sperm abnormalities to obtain studies giving any evidence for their efficacy and pharmacological mechanisms related to male infertility. Data were collected for the years 1966 to March 2015. For some of them, including Chlorophytum borivilianum, Crocus sativus, Nigella sativa, Sesamum indicum, Tribulus terrestris, Mucuna pruriens and Withania somnifera, more reliable evidence was found. The mechanisms involved in the beneficial effects of medicinal plants in sperm abnormalities are antioxidant, anti‐inflammatory, anti‐oedematous and venotonic activity as well as containing precursors for sperm production and increasing blood testosterone level. Various phytochemical categories including saponins, phytosterols, carotenoids, oxygenated volatile compounds, phenolic compounds and alkaloids seem to be responsible for these beneficial effects. Further studies are recommended for obtaining more conclusive results about the efficacy and safety of the mentioned medicinal plants.